METHODS FOR COMPILING TEXTBOOKS OF JAPANESE ECONOMIC AND TRADE TRANSLATION AT HANOI UNIVERSITY (Journal of Foreign Language Studies, 2021)
Economic and Trade Translation is one of the specialized modules in Japanese language undergraduate program at Hanoi University. This course aims to equip learners with fundamental translation theories, particularly translation in the field of trade and economy, grammar structures and lexis frequently used in trade and economy and translation techniques to facilitate their economic and trade translation. A set of teaching materials compiled by the lecturers are utilized in this course; however, the learning objectives and expected outcomes have yet been achieved due to the limitations in teaching contents. This paper focuses on offering directions for the development of textbooks on economic and trade translation at Hanoi University, including defining the aims and requirements, specifying the structure of the contents, choosing and organizing corpora ... to ensure the quality and scientificity of the textbooks.
Keywords: Economic and trade translation textbook; development method; orientation